Seeing the Landscape: Multiple Scales of Visualising Terrestrial Heritage on Rosemary Island (Dampier Archipelago). (4th September 2020) - McDonald, Jo; Beckett, Emma; Hacker, Jorg; Morrison, Patrick; O'Leary, Michael
The Dampier Archipelago (Murujuga) is on Australia's National Heritage List because of its significant rock art and numerous stone structures. When people first started living in this arid landscape of the north-west coast, 50, 000 years ago, the shoreline was 160 kilometres further north-and west. The Archipelago was created around 7, 000 years ago, with sea-level rise following the termination of the Last Glacial Maximum (LGM). Photogrammetry and microphotography (using LiDAR, RPA and Dino-Lite™) are used here to demonstrate how this combination of different scales of imaging can be used to better document the terrestrial Murujuga features record. This paper explores the utility of photogrammetry generated by LiDAR and RPA to locate and reconstruct two types of Aboriginal stone structure (standing stones and house structures) which are prevalent across the Archipelago. These combined techniques were deployed to better visualise and understand site distribution with a view to using the landscape scale methods for the detection of similar features in submerged contexts in the adjacent waters. It has been predicted that this more robust site type would be likely to survive being submerged by sea level rise, and hence this was a site type which we were interested in locating remotely. As well as undertaking systematic terrestrial survey and recording of sample areas across Rosemary Island, topographic LiDAR was flown on two occasions (2017, 2018). These flights were separated by a wildfire which burnt most of the spinifex cover across the island. It highlights the potential – and shortcomings – of remote sensing this type of cultural sites in a naturally rocky and spinifex-covered landscape. It makes recommendations about how to better implement LiDAR to assist in the understanding of the landscape context of these hunter-gatherer stone features.